MULTILINGUALISM AND SOCIAL STRATEGIES USED BY ENGLISH TEACHERS IN SAWAHLUNTO - Ika Lasmiatun; Suswati Hendriani (Universitas Negeri Padang, 2016)
Multilingualism and multiculturalism- exists in many parts of the world today, including in Sawahlunto. In that city, people come from different cultures and use different languages, namely: Javanese, Sundanese, Bataknese, Minangkabaunese, and Acehnese. It cannot be denied that in such a society, people are constantly creating on and using multiple languages. In fact, multilingualism -and multiculturalism- has been a big issue in the world of language education, especially in English language teaching. To teach English to the multilingual students, the English teachers must understand the connection between students’ languages, and their cultures. This will develop the teachers’ awareness of the social dimensions of language use which will be an important component in their English language teaching. This awareness will help them to use different social teaching strategies to approach the languages as mediating tools for teaching English as communication. In other words, the languages, then, are not exclusively objects of teaching but a means of communication and interaction. This paper is aimed to find out teachers’ social strategies to teach English to multilingual students in Sawahlunto. This is a descriptive research with a cross-sectional design. The data are collected through a questionnaire. The data analysis is done by using SPSS 22 version.